KETERBUKAAN KOMUNIKASI DALAM KONSELING PROGRAM PIK-R CERIA SENTUL - Widyasari, Nurul Azmi; Sukarelawati, Sukarelawati; Fitriah, Maria (JURNAL KOMUNIKATIO, 2019)
Openness is the willingness of people to disclose information about themselves that might normally be hidden, provided that there are only a few appropriate disclosures (Devito, 2007). Openness in communication plays an important role in the counseling process. According to Sri Hastuti and Winkel (2007), counseling is giving advice in an interaction by exchanging ideas. With the openness in the counseling process, the purpose of a counseling will be easily achieved. This study aims to analyze the communication openness in the Ceria Sentul PIK-R counseling program. This study uses a descriptive type method with a quantitative approach carried out by survey using data collection techniques. Primary data consists of the results of observations and questionnaires, while secondary data in the form of results from library studies, documentation and interviews. The results of the study were processed using a single data tabulation. The study sample was determined by nonprobability sampling technique and the sample used was taken from the population of ideal adolescents aged 10-24 years who had joined the Ceria Sentul PIK-R counseling activity. Sampling was determined using accidental sampling technique with a total sample of 30 respondents scattered in the CIKI Sentul PIK-R counseling activity. The results showed that the openness of communication in Ceria Sentul's PIK-R counseling program had a good category. This can be seen from the majority of respondents who agree that openness is in the counseling process. The conclusion of this study is that the client is ready to be open or ready to open himself to the counselor. Â Keywords: Communication; Openness; Counseling